A coating slurry for reducing cracking and warping of negative electrode coating and a preparation method thereof

By using ethanol and butylene glycol as composite solvents in the negative electrode coating slurry of lithium battery, the problems of cracking and low volatility of the negative electrode coating are solved, and higher battery performance and lower production costs are achieved .

CN115148944BActive Publication Date: 2025-01-10HU ZHOU YAO NING GU TAI DIAN CHI YAN JIU YUAN YOU XIAN GONG SI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210488471.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-06
Publication Date
2025-01-10
Estimated Expiration
2042-05-06

AI Technical Summary

Technical Problem

During the lithium battery manufacturing process, negative electrode coating is prone to cracking and warping, and the volatility efficiency of existing organic solvents is low, resulting in battery performance loss and production costs.

Method used

Ethanol and butylene glycol are used as composite solvents, with a mass ratio of 0.15:0.85 to 0.25:0.75. Add to the negative electrode coating slurry to improve the solvent volatility rate and uniformity, reduce solvent residue, and prevent the electrode sheet from cracking and warping.

Benefits of technology

It effectively reduces the cracking and warping of the negative electrode sheet, improves the first-time efficiency and capacity of the battery, reduces production costs, and improves the coating pass rate and first-time efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the field of lithium-ion battery materials, and discloses a coating slurry for reducing cracking and warping of negative electrode coating and a preparation method thereof, comprising 50% to 60% by mass of solid powder and 40% to 50% by mass of solvent, wherein the solvent is a mixture of deionized water, ethanol and butanediol, the total mass of ethanol and butanediol is 1% to 3% of the total mass of the solid powder, and the mass ratio of ethanol to butanediol is 0.15:0.85 to 0.25:0.75. The preparation method comprises the following steps: (1) premixing; (2) kneading; (3) primary dispersion; (4) secondary dispersion; (5) mixing. A specific proportion of ethanol and butanediol is added to the negative electrode coating slurry formula to accelerate the volatilization speed, improve the volatilization uniformity, and reduce the cracking and warping of the negative electrode sheet; a specific mixing process is used to mix the materials, and finally a volatile organic solvent is added to ensure that the solid content and uniformity of the coating slurry meet the requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of lithium ion battery materials, and in particular to a coating slurry for reducing cracking and warping of negative electrode coating and a preparation method thereof. Background Art

[0002] In the manufacturing process of lithium batteries, negative electrode coating is a key process. Negative electrode coating is to evenly coat the negative electrode slurry on the substrate through extrusion coating, transfer coating, spraying and other coating methods, and dry it in a negative pressure and high temperature environment in an oven to remove the solvent in the negative electrode slurry and obtain solid powder adhering to the substrate. At present, copper foil is generally used as the substrate, and some negative electrode materials use aluminum foil as the substrate.

[0003] During the solvent volatilization process, due to the different volatilization speeds of the inner layer and the surface solvent, when the surface solvent evaporates quickly, the inner layer solvent has not yet volatilized, resulting in a certain temperature difference between the inner layer and the surface, causing the electrodes in these two areas to crack. Also, because there are thinning areas and normal areas along the coating width, and the dressing weight in the thinning area is 2-5% lower than that in the normal area, when the electrode is dried at the same time and environment, the drying speed of the thinning area is greater than that of the normal area. When the time difference between the two is large, the electrode will warp. Both of these undesirable phenomena will affect the product qualification rate of the negative electrode, and with the rapid increase in coating speed and the emergence of production methods such as double-sided coating, the frequency of these two undesirable phenomena has also greatly increased, which has a significant impact on the coating qualification rate.

[0004] At present, there are two main methods in the industry to improve the cracking and warping of the pole piece during negative electrode coating. One is to adjust the temperature, air volume, coating speed and other parameters of the oven to dry the negative electrode under reasonable parameters to improve the state of the pole piece. However, because the slurry state is different each time, the parameters must be adjusted frequently, which brings great unpredictability to production. Another method is to add an organic solvent to the negative electrode slurry to reduce the boiling point of the solvent in the negative electrode slurry and increase the overall volatilization rate of the solvent. For example, Chinese patent publication number "CN114335528A" discloses a negative electrode glue and its preparation method and application, and the negative electrode glue includes: sodium carboxymethyl cellulose, N-methyl pyrrolidone and water. By mixing N-methyl pyrrolidone and sodium carboxymethyl cellulose with water as a negative electrode glue, on the one hand, it can solve the problem of film cracking of graphite negative electrode slurry, and on the other hand, it can effectively reduce the surface tension of graphite negative electrode slurry and improve the problem of graphite and water infiltration, thereby greatly improving the negative electrode coating production efficiency. However, the problem with this type of method is that conventional organic solvents are N-methylpyrrolidone (NMP) or ethylene carbonate (EC). When these two solvents cannot fully evaporate, they will remain inside the electrode, causing certain losses to the initial effect and capacity of the battery. In addition, when using NMP as a solvent, an NMP recovery device needs to be added. If there is no NMP recovery device, the NMP concentration in the oven will be too high, which may cause an explosion accident, so the production cost is greatly increased. EC is solid at room temperature and needs to be heated to above 35°C before use, which also requires additional production costs. Summary of the invention

[0005] The present invention aims to overcome the problems in the prior art that negative electrode coating is prone to cracking and warping and the existing organic solvent has low volatilization efficiency. A coating slurry for reducing cracking and warping of negative electrode coating and a preparation method thereof are provided. Ethanol and butanediol are used as composite solvents to enhance solvent volatility and uniformity. On the one hand, the influence of solvent residue on the primary effect and capacity of the electrode is reduced. On the other hand, cracking and warping of the electrode caused by uneven solvent volatilization is prevented.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A coating slurry for reducing cracking and warping of negative electrode coating, comprising 50% to 60% by mass of solid powder and 40% to 50% by mass of solvent, wherein the solvent is a mixture of deionized water, ethanol and butanediol, wherein the total mass of the ethanol and butanediol is 1% to 3% of the total mass of the solid powder, and the mass ratio of the ethanol to butanediol is 0.15:0.85 to 0.25:0.75. Preferably, the mass fraction of the solid powder in the coating slurry is 50% to 55%.

[0008] In the process of negative electrode coating, ethanol and butanediol with better volatility are added to the solvent, which can accelerate the volatilization rate of the solvent, enhance the uniformity of the solvent volatilization, and avoid the bad phenomenon of the pole piece caused by the difference in volatilization rate in different regions. At the same time, due to the better volatility of ethanol and butanediol compared with traditional organic additives, the residues of these two substances in the negative electrode sheet are lower, and the impact on battery performance is smaller. The prepared negative electrode sheet can improve the first efficiency and capacity of the battery. Among these two organic solvents, although ethanol has a lower boiling point and better volatility, due to its relatively poor thermal stability, excessive addition of ethanol may lead to the production of some difficult-to-volatilize byproducts, resulting in reduced battery performance; if the amount of ethanol added is insufficient, the degree of improvement of the solvent volatility is limited. The mass ratio of ethanol to butanediol is between 0.15:0.85 and 0.25:0.75, which can not only meet the requirements of volatilization rate and uniformity, but also ensure its stability during coating and subsequent drying.

[0009] Preferably, the solid powder comprises the following raw materials in parts by weight: 92 to 98 parts of graphite, 0.4 to 5 parts of conductive agent, 1.3 to 1.7 parts of binder, and 0.8 to 1.3 parts of thickener.

[0010] Preferably, the graphite is one of artificial graphite, mesophase graphite, natural graphite, silicon carbon, soft carbon, hard carbon or a combination thereof.

[0011] Preferably, the conductive agent is one of carbon black, Ketjen black, flake graphite conductive agent, carbon nanotube, graphene or a combination thereof.

[0012] Preferably, the thickener is sodium carboxymethyl cellulose, and the binder is one or a combination of polyacrylic acid, polyacrylonitrile, and styrene-butadiene rubber.

[0013] A method for preparing a coating slurry for reducing cracking and warping of negative electrode coating comprises the following steps:

[0014] (1) Premixing: Add graphite, conductive agent, and 35-45% thickener into a stirrer in sequence, stir and mix for 30-60 minutes, then stop stirring to obtain a premix;

[0015] (2) kneading: adding deionized water to the premix until the solid content is 66-74%, and then stirring and kneading for 60-90 minutes to obtain a kneaded material;

[0016] (3) Primary dispersion: Add the remaining thickener to the kneaded material, and then add deionized water to a solid content of 56-60%. The stirring blade of the stirrer rotates and moves in the material to perform primary dispersion. The dispersion time is 87-93 minutes to obtain a primary dispersion slurry.

[0017] (4) Secondary dispersion: Add the binder and the remaining deionized water to the primary dispersion slurry, and rotate the stirring blade of the agitator while moving in the material to perform secondary dispersion. The dispersion time is 30 to 45 minutes to obtain a secondary dispersion slurry.

[0018] (5) Mixing: Add the pre-mixed ethanol and butanediol to the secondary dispersion slurry, and stir evenly to obtain a coating slurry that reduces cracking and warping of the negative electrode coating.

[0019] In the preparation process of the coating slurry, the addition time and order of each component have a direct impact on the quality of the final coating slurry. In the preparation process of the present invention, graphite, conductive agent and part of the thickener are first premixed to ensure that the graphite and the conductive agent are evenly mixed before adding part of the deionized water for kneading. The kneading process is to first mix the material evenly with part of the deionized water at a higher solid content, and then add the remaining thickener and deionized water for dispersion. If all the thickeners and deionized water are directly added to the powder for mixing, the viscosity difference at various places may be too large due to the large amount of thickeners added, affecting the dispersion of graphite and conductive agent. After the remaining thickener is added, the viscosity of the material is reduced. On the one hand, the local material is mixed by rotating the stirring paddle in the preparation process, and on the other hand, the uniformity of the dispersion of the whole material is ensured by the movement of the stirring paddle in the material. After all the thickeners are added, the binder and the remaining deionized water are added, and the solids in the slurry are formed into a whole through the action of the binder. Finally, organic solvents such as ethanol and butanediol are added to the slurry to reduce the dispersion time of organic matter in the system and avoid dispersion of organic matter due to long-term volatilization. At the same time, since ethanol and butanediol are liquids at room temperature, they can be put into production without pretreatment, and the cost is lower than other organic solvents.

[0020] Preferably, in step (3), the viscosity of the primary dispersion slurry is 5000-8000 mPa·s. If the viscosity of the primary dispersion slurry is too low, the prepared coating slurry may be too thin, and the solid content on the negative electrode sheet after coating may be too low; if the viscosity of the primary dispersion slurry is too high, it may increase the difficulty of stirring in the subsequent preparation process, resulting in poor slurry uniformity and increased coating difficulty.

[0021] Preferably, in step (1), the rotation speed of the stirring paddle of the agitator is 20 to 35 rpm; in step (2), the rotation speed of the stirring paddle of the agitator is 20 to 30 rpm.

[0022] Preferably, in step (3), the rotation speed of the stirring paddle of the agitator is 20 to 35 rpm, and the moving speed of the stirring paddle is 13 to 18 m / s.

[0023] Preferably, in step (4), the rotation speed of the stirring paddle of the agitator is 20 to 35 rpm, and the moving speed of the stirring paddle is 6 to 10 m / s.

[0024] Therefore, the present invention has the following beneficial effects: (1) a composite organic solvent system is added to the negative electrode coating slurry formula, comprising ethanol and butanediol in a specific proportion, and the good volatility of the organic solvent is utilized to accelerate the volatilization speed and volatilization uniformity, thereby reducing the cracking and warping of the negative electrode sheet; (2) a specific mixing process is used to mix the materials during the preparation of the coating slurry, and finally a volatile organic solvent is added, so that the solid content and uniformity of the coating slurry meet the requirements. DETAILED DESCRIPTION

[0025] The present invention is further described below in conjunction with specific embodiments. It should be understood that these embodiments are suitable for illustrating the basic principles, main features and advantages of the present invention, and the present invention is not limited by the scope of the following embodiments; the implementation conditions used in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions used in conventional experiments.

[0026] Unless otherwise specified in the following examples, all raw materials are commercially available or prepared by conventional methods in the art.

[0027] Example 1

[0028] A coating slurry for reducing cracking and warping of negative electrode coating comprises 50% by mass of solid powder and 50% by mass of solvent, wherein the solid powder comprises the following raw materials in parts by weight: 96.5 parts of artificial graphite, 1 part of conductive agent carbon black, 1 part of thickener sodium carboxymethyl cellulose, 1.5 parts of binder styrene-butadiene rubber, and the solvent is a mixture of deionized water, ethanol and butanediol, wherein the total mass of ethanol and butanediol is 1.5% of the total mass of the solid powder, and the mass ratio of ethanol to butanediol is 0.2:0.8.

[0029] The method for preparing a coating slurry for reducing cracking and warping of negative electrode coating comprises the following steps:

[0030] (1) Premixing: Add graphite, conductive agent and 40% thickener into a stirrer in sequence, stir and mix for 45 minutes at a stirring speed of 30 rpm to obtain a premix;

[0031] (2) kneading: adding deionized water to the premix until the solid content is 70%, stirring and kneading, the stirring blade speed of the stirrer is 25 rpm, and the time is 75 minutes to obtain a kneaded material;

[0032] (3) Primary dispersion: Add the remaining thickener to the kneaded material, and then add deionized water to a solid content of 58%. The stirring blade of the stirrer rotates and moves in the material at the same time. The stirring blade speed of the stirrer is 30 rpm and the moving speed of the stirring blade is 15 m / s. The primary dispersion is performed for 90 min to obtain a primary dispersion slurry. The viscosity of the primary dispersion slurry is 5000 to 8000 mPa·s.

[0033] (4) Secondary dispersion: Add the binder and the remaining deionized water to the primary dispersion slurry, rotate the stirring blade of the stirrer while moving in the material, the stirring blade speed of the stirrer is 30 rpm, the stirring blade movement speed is 8 m / s, and secondary dispersion is performed for 40 min to obtain a secondary dispersion slurry;

[0034] (5) Mixing: Add the pre-mixed ethanol and butanediol to the secondary dispersion slurry, and stir evenly to obtain a coating slurry that reduces cracking and warping of the negative electrode coating.

[0035] Example 2

[0036] A coating slurry for reducing cracking and warping of negative electrode coating comprises 55% by mass of solid powder and 45% by mass of solvent, wherein the solid powder comprises the following raw materials in parts by weight: 92 parts of natural graphite, 0.4 parts of conductive agent Ketjen black, 0.8 parts of thickener sodium carboxymethyl cellulose, and 1.3 parts of binder polyacrylic acid, and the solvent is a mixture of deionized water, ethanol and butanediol, wherein the total mass of ethanol and butanediol is 3% of the total mass of the solid powder, and the mass ratio of ethanol to butanediol is 0.25:0.75.

[0037] The method for preparing a coating slurry for reducing cracking and warping of negative electrode coating comprises the following steps:

[0038] (1) Premixing: Add graphite, conductive agent and 35% thickener into a stirrer in sequence, stir and mix for 30 minutes at a stirring speed of 35 rpm to obtain a premix;

[0039] (2) kneading: adding deionized water to the premix until the solid content is 74%, and then stirring and kneading, the stirring blade speed of the stirrer is 20 rpm, and the time is 90 minutes to obtain a kneaded material;

[0040] (3) Primary dispersion: the remaining thickener is added to the kneaded material, and then deionized water is added to the kneaded material until the solid content is 60%. The stirring blade of the stirrer rotates and moves in the material at the same time. The stirring blade speed of the stirrer is 35 rpm and the moving speed of the stirring blade is 18 m / s. The primary dispersion is performed for 87 min to obtain a primary dispersion slurry. The viscosity of the primary dispersion slurry is 5000 to 8000 mPa·s.

[0041] (4) Secondary dispersion: Add the binder and the remaining deionized water to the primary dispersion slurry, rotate the stirring blade of the stirrer while moving in the material, the stirring blade speed of the stirrer is 35 rpm, the stirring blade movement speed is 10 m / s, and secondary dispersion is performed for 30 min to obtain a secondary dispersion slurry;

[0042] (5) Mixing: Add the pre-mixed ethanol and butanediol to the secondary dispersion slurry, and stir evenly to obtain a coating slurry that reduces cracking and warping of the negative electrode coating.

[0043] Example 3

[0044] A coating slurry for reducing cracking and warping of negative electrode coating comprises 60% by mass of solid powder and 40% by mass of solvent, wherein the solid powder comprises the following raw materials in parts by weight: 98 parts of silicon carbon, 5 parts of conductive agent carbon nanotubes, 1.3 parts of thickener sodium carboxymethyl cellulose, and 1.7 parts of binder polyacrylonitrile, and the solvent is a mixture of deionized water, ethanol and butanediol, wherein the total mass of ethanol and butanediol is 1% of the total mass of the solid powder, and the mass ratio of ethanol to butanediol is 0.15:0.85.

[0045] The method for preparing a coating slurry for reducing cracking and warping of negative electrode coating comprises the following steps:

[0046] (1) Premixing: Add graphite, conductive agent and 45% thickener into a stirrer in sequence, stir and mix for 90 minutes at a stirring speed of 20 rpm to obtain a premix;

[0047] (2) kneading: adding deionized water to the premix until the solid content is 66%, stirring and kneading, the stirring blade speed of the stirrer is 30 rpm, and the time is 87 minutes to obtain a kneaded material;

[0048] (3) Primary dispersion: the remaining thickener is added to the kneaded material, and then deionized water is added to the solid content of 56%. The stirring blade of the stirrer rotates and moves in the material at the same time. The stirring blade speed of the stirrer is 20 rpm and the moving speed of the stirring blade is 13 m / s. The primary dispersion is performed for 87 min to obtain a primary dispersion slurry. The viscosity of the primary dispersion slurry is 5000 to 8000 mPa·s.

[0049] (4) Secondary dispersion: Add the binder and the remaining deionized water to the primary dispersion slurry, rotate the stirring blade of the stirrer while moving in the material, the stirring blade speed of the stirrer is 20 rpm, the stirring blade movement speed is 6 m / s, and secondary dispersion is performed for 45 min to obtain a secondary dispersion slurry;

[0050] (5) Mixing: Add the pre-mixed ethanol and butanediol to the secondary dispersion slurry, and stir evenly to obtain a coating slurry that reduces cracking and warping of the negative electrode coating.

[0051] Example 4

[0052] A coating slurry for reducing cracking and warping of negative electrode coating comprises 50% by mass of solid powder and 50% by mass of solvent, wherein the solid powder comprises the following raw materials in parts by weight: 96 parts of intermediate phase graphite and soft carbon in a mass ratio of 5:1, 3 parts of conductive agent graphene, 1 part of thickener sodium carboxymethyl cellulose, 1.4 parts of polyacrylic acid and styrene-butadiene rubber in a mass ratio of 1:1 as binder, and the solvent is a mixture of deionized water, ethanol and butanediol, wherein the total mass of ethanol and butanediol is 2% of the total mass of the solid powder, and the mass ratio of ethanol to butanediol is 0.2:0.8.

[0053] Example 5

[0054] A coating slurry for reducing cracking and warping of negative electrode coating comprises 50% by mass of solid powder and 50% by mass of solvent, wherein the solid powder comprises the following raw materials in parts by weight: 96.5 parts of hard carbon, 4 parts of carbon black and flaky graphite in a conductive agent mass ratio of 1:1, 1.2 parts of sodium carboxymethyl cellulose as a thickener, and 1.4 parts of styrene-butadiene rubber as a binder, and the solvent is a mixture of deionized water, ethanol and butanediol, wherein the total mass of ethanol and butanediol is 2.5% of the total mass of the solid powder, and the mass ratio of ethanol to butanediol is 0.2:0.8.

[0055] Example 6

[0056] The only difference between this embodiment and embodiment 1 is that the total mass of ethanol and butanediol is 1% of the total mass of the solid powder.

[0057] Example 7

[0058] The only difference between this embodiment and embodiment 1 is that the total mass of ethanol and butanediol is 2.5% of the total mass of the solid powder.

[0059] Example 8

[0060] The only difference between this embodiment and embodiment 1 is that the total mass of ethanol and butanediol is 3% of the total mass of the solid powder.

[0061] Example 9

[0062] The only difference between this embodiment and embodiment 1 is that the total mass of ethanol and butanediol is 2% of the total mass of the solid powder.

[0063] Comparative Example 1 (without adding composite organic solvent)

[0064] The only difference between this comparative example and Example 1 is that the ethanol and butanediol in the solvent are replaced with deionized water of equal mass.

[0065] Comparative Example 2 (using the same mass of NMP instead of organic solvent)

[0066] The only difference between this comparative example and Example 1 is that the ethanol and butanediol in the solvent are replaced by N-methylpyrrolidone of the same mass.

[0067] Comparative Example 3 (using a large amount of NMP instead of organic solvent)

[0068] The only difference between this comparative example and Example 1 is that the ethanol and butanediol in the solvent are replaced by 5% of the total weight of the solid powder with N-methylpyrrolidone.

[0069] Comparative Example 4 (using the same mass of EC instead of organic solvent)

[0070] The only difference between this comparative example and Example 1 is that the ethanol and butanediol in the solvent are replaced by an equal mass of ethylene carbonate, and in step (5) of the preparation process, the ethylene carbonate is first preheated to 35° C. to melt into a liquid, and then added to the secondary dispersion slurry.

[0071] Comparative Example 5 (using a large amount of EC instead of organic solvent)

[0072] The only difference between this comparative example and Example 1 is that the ethanol and butanediol in the solvent are replaced by ethylene carbonate accounting for 5% of the total weight of the solid powder, and in step (5) of the preparation process, the ethylene carbonate is first preheated to 35°C to melt into a liquid and then added to the secondary dispersion slurry.

[0073] Comparative Example 6 (addition of only butanediol)

[0074] The only difference between this comparative example and Example 1 is that the ethanol in the solvent is replaced with deionized water of the same mass.

[0075] Comparative Example 7 (addition of ethanol only)

[0076] The only difference between this comparative example and Example 1 is that the butanediol in the solvent is replaced with deionized water of the same mass.

[0077] Comparative Example 8 (no step-by-step feeding during the preparation process)

[0078] The difference between this comparative example and Example 1 is that steps (2) and (3) are not performed during the preparation process, and all the thickener and deionized water are directly added in step 1.

[0079] The negative electrode coating materials prepared in Examples 1-9 of the present invention and Comparative Examples 1-6 were uniformly coated on copper foil using a transfer coater, with a coating speed of 15 m / min, an oven temperature of 80° C., and an oven air volume of 30 Hz. The cracking, warping, coating pass rate, and first efficiency of the obtained negative electrode sheets were measured. The test results are shown in Table 1.

[0080] Table 1 Cracking and warping of negative electrode sheet and initial efficiency

[0081] Group Cracking Warpage Coating pass rate (%) First efficiency (%) Example 1 No cracking No warping 94.5 90.1 Example 2 No cracking No warping 94.6 89.8 Example 3 No cracking No warping 94.5 89.9 Example 4 No cracking No warping 94.4 90 Example 5 No cracking No warping 94.2 89.1 Example 6 No cracking No warping 94.1 89.7 Example 7 No cracking No warping 94.7 89.8 Example 8 No cracking No warping 94.0 90.0 Example 9 No cracking No warping 94.4 89.7 Comparative Example 1 Cracking Warping 90.1 89.8 Comparative Example 2 Cracking Warping 91.5 87.5 Comparative Example 3 No cracking No warping 94.5 85.8 Comparative Example 4 Cracking Warping 91.4 88.2 Comparative Example 5 No cracking No warping 94.1 86.4 Comparative Example 6 Cracking Warping 92.1 89.8 Comparative Example 7 Cracking Warping 92.3 88.9 Comparative Example 8 No cracking No warping 93.5 89.4

[0082] It can be seen from Examples 1-5 in the above table that the negative electrode coating slurry prepared according to the method described in the present invention has a faster drying efficiency during the coating process, and the quality of the prepared negative electrode sheet is better, without undesirable phenomena such as cracking and warping. The coating qualified rate can reach about 94%, and the first efficiency can also reach about 90%, indicating that the added composite organic solvent has less residue and has little effect on the performance of the negative electrode sheet.

[0083] Comparative Examples 1-8 are set up based on Example 1, which has the best comprehensive performance among the above 7 embodiments. In the preparation process of Comparative Example 1, no organic solvent is added, and the coating slurry prepared by it is difficult to dry evenly during the drying process, so the negative electrode sheet is prone to obvious cracking or warping and other undesirable phenomena, which seriously affects the coating qualification rate of the negative electrode sheet. Comparative Examples 2 and Comparative Examples 4 respectively use N-methylpyrrolidone and ethylene carbonate of equal mass to replace the composite organic solvent and add them to the negative electrode coating slurry, but these two substances still cannot completely improve the cracking and warping phenomena that occur during the negative electrode coating process under this addition amount, and the coating qualification rate is not high. Comparative Examples 3 and Comparative Examples 5 can overcome the problems of solvent volatility and uniformity by increasing the addition amount of both, and avoid the problems of cracking and warping, but due to the poor solvent volatility performance, the first efficiency of the prepared negative electrode sheet is lower than that of Examples 1-9, which has a great impact on the performance of the negative electrode sheet. Comparative Example 6 only adds butanediol, which has limited improvement on the cracking and warping of the negative electrode sheet, and its coating qualification rate is low. In Comparative Example 7, only ethanol is added. Although the cracking and warping of the negative electrode sheet can be improved, due to the thermal stability of ethanol, if the amount added is too high, various impurities are easily formed during the drying process, which reduces the initial efficiency of the negative electrode sheet and affects the performance of the negative electrode sheet. In Comparative Example 8, the materials are directly mixed during the preparation of the negative electrode slurry, and the control of the dilution degree and viscosity of the materials is not accurate enough, which easily causes the prepared slurry to have problems such as excessive solid content and excessive viscosity, affecting the uniformity of the coating, and also affecting the volatilization of the solvent in the subsequent drying process. Therefore, the prepared negative electrode sheet is inferior to Examples 1-9 in both appearance and performance.

Claims

1. A method for preparing a coating slurry for reducing cracking and warping of negative electrode coating, characterized in that: The following steps are involved: (1) Premixing: Add graphite, conductive agent, and 35-45% thickener into a stirrer in sequence, stir and mix for 30-60 minutes, then stop stirring to obtain a premix; (2) Kneading: Add deionized water to the premix until the solid content is 66-74%, and then stir and knead for 60-90 min to obtain a kneaded material; (3) Primary dispersion: Add the remaining thickener to the kneaded material, and then add deionized water to a solid content of 56-60%. The stirring paddle of the agitator rotates and moves in the material to perform primary dispersion. The dispersion time is 87-93 min to obtain a primary dispersion slurry. (4) Secondary dispersion: Add the binder and the remaining deionized water to the primary dispersion slurry, and rotate the stirring paddle of the agitator while moving in the material to perform secondary dispersion. The dispersion time is 30 to 45 minutes to obtain a secondary dispersion slurry. (5) Mixing: Add pre-mixed ethanol and butanediol to the secondary dispersion slurry, stir evenly to obtain a coating slurry that reduces cracking and warping of the negative electrode coating; the coating slurry includes 50% to 60% by mass of solid powder and 40% to 50% by mass of solvent; the solvent is a mixture of deionized water, ethanol and butanediol; the total mass of ethanol and butanediol is 1% to 3% of the total mass of the solid powder, and the mass ratio of ethanol to butanediol is 0.15:0.85 to 0.25:0.

75.

2. The method for preparing a coating slurry for reducing cracking and warping of negative electrode coating according to claim 1, characterized in that: The solid powder comprises the following raw materials in parts by weight: 92-98 parts of graphite, 0.4-5 parts of conductive agent, 1.3-1.7 parts of binder, and 0.8-1.3 parts of thickener.

3. The method for preparing a coating slurry for reducing cracking and warping of negative electrode coating according to claim 1, characterized in that: The graphite is one of artificial graphite, mesophase graphite, and natural graphite, or a combination thereof.

4. The method for preparing a coating slurry for reducing cracking and warping of negative electrode coating according to claim 1, characterized in that: The conductive agent is one of carbon black, Ketjen black, flake graphite conductive agent, carbon nanotube, graphene or a combination thereof.

5. The method for preparing a coating slurry for reducing cracking and warping of negative electrode coating according to claim 1, characterized in that: The thickener is sodium carboxymethyl cellulose, and the binder is one of polyacrylic acid, polyacrylonitrile, styrene-butadiene rubber or a combination thereof.

6. The method for preparing a coating slurry for reducing cracking and warping of negative electrode coating according to claim 1, characterized in that: In the step (3), the viscosity of the primary dispersed slurry is 5000-8000 mPa·s.

7. The method for preparing a coating slurry for reducing cracking and warping of negative electrode coating according to claim 1, characterized in that: In the step (1), the stirring blade speed of the agitator is 20-35 rpm; in the step (2), the stirring blade speed of the agitator is 20-30 rpm.

8. The method for preparing a coating slurry for reducing cracking and warping of negative electrode coating according to claim 1, characterized in that: In the step (3), the stirring blade speed of the agitator is 20-35 rpm, and the moving speed of the stirring blade is 13-18 m / s.

9. The method for preparing a coating slurry for reducing cracking and warping of negative electrode coating according to claim 1, characterized in that: In the step (4), the stirring blade speed of the agitator is 20-35 rpm, and the moving speed of the stirring blade is 6-10 m / s.

Citation Information

Patent Citations

  • Negative electrode glue solution as well as preparation method and application thereof

    CN114335528A

  • Lithium ion battery pole piece slurry, pole piece and preparation method and application thereof

    CN110459773A